2011
DOI: 10.1590/s1984-29612011000200006
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory response indicators in rabbits (Oryctolagus cuniculus) experimentally infected with sporulated oocysts of Eimeria stiedai (Apicomplexa: Eimeriidae)

Abstract: Hemograms and acute-phase proteins in adult male New Zealand White rabbits that had been experimentally infected orally with sporulated oocysts of Eimeria stiedai were evaluated over a 28-day period. Fifty animals were used, divided into two groups: group A infected with 1 × 10(4) sporulated oocysts of E. stiedai and group B inoculated with distilled water. On the seventh day after infection, the infected animals presented anemia and leukocytosis with neutrophilia and monocytosis. Protein fractionation by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
2
6
0
1
Order By: Relevance
“…To our knowledge, our study is the first to examine the relationship between Hp and SAA levels and experimental infections with Eimeria in cattle, although studies on SAA and Hp levels in response to Eimeria infection have been performed in rabbits and goats. Rabbits infected with 10,000 Eimeria stiedai oocysts were reported by Freitas et al (2011) to exhibit increased APP concentrations of ceruloplasmin, transferrin and Hp from 7 to 28 days post-infection. Infection of goat kids with 1,000 or 100,000 sporulated Eimeria arloingi oocysts was also reported to increase blood levels of Hp and SAA (Hashemnia et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our study is the first to examine the relationship between Hp and SAA levels and experimental infections with Eimeria in cattle, although studies on SAA and Hp levels in response to Eimeria infection have been performed in rabbits and goats. Rabbits infected with 10,000 Eimeria stiedai oocysts were reported by Freitas et al (2011) to exhibit increased APP concentrations of ceruloplasmin, transferrin and Hp from 7 to 28 days post-infection. Infection of goat kids with 1,000 or 100,000 sporulated Eimeria arloingi oocysts was also reported to increase blood levels of Hp and SAA (Hashemnia et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Serum bilirubin levels can rise to 305 mg/ dl, increasing as soon as day 6 of infection and increasing through days 20-24 before moderating (Rose, 1959). Leukocytosis and anemia can be observed and acute phase proteins are notably increased by 7 days post infection (Freitas et al, 2011). Diagnosis can be made by examination of fecal material, by either flotation or concentration methods.…”
Section: Hepatic Coccidiosismentioning
confidence: 99%
“…In this study, a significant increase in PFA was found two months before the animals showed clinical signs (MARTINEZ-SUBIELA et al, 2014). Additionally, the analysis of PFA has yielded promising results in autoimmune disorders in calves (BEZUIDENHOUT & PRETORIUS, 2020), infectious diseases in cats and dogs (PALTRINIERI et al, 2007;KOCATURK et al, 2010), parasitic diseases in rabbits and dogs (FREITAS, 2011;MYLONAKIS et al, 2012;CÉRON et al 2018) and tumoral diseases in cats (SELTING et al, 2000). However, the correlation between these proteins and trauma is not yet fully understood (CHRISTENSEN et al, 2015).…”
Section: Clinic and Surgerymentioning
confidence: 58%